Pathology of Fatal Australian Black Snake (Pseudechis sp) Envenomation in Two Adult Dogs. (July 2021) - Kelly-Bosma, Mirrim; Leister, Ellie; Padula, Andrew; Schaffer-White, Andrea; Bielefeldt-Ohmann, Helle; Haworth, Mark; Henning, Joerg; Allavena, Rachel
Summary: Black snakes ( Pseudechis spp) are a genus of venomous Australian elapid snakes that can cause major clinical envenomation in companion animals, which may be fatal, even with appropriate antivenom treatment. Despite its clinical significance, there is little published information on the pathology of black snake envenomation. We report the gross and microscopic lesions associated with black snake envenomation in two dogs, one with a definitive immunological species identification of red-bellied black snake (RBBS; Pseudechis porphyriacus ), the other with a black snake immunotype on a venom detection kit. Both dogs were located in a geographical area where the RBBS is found. The prominent gross findings in both cases included icterus, localized facial oedema in the region of the presumed bite wound, pigmenturia and multicavitary serosanguineous effusions. Histopathology of the confirmed RBBS case revealed acute renal tubular necrosis with haemosiderosis, marked splenic haemosiderosis and centrilobular to midzonal hepatocellular necrosis with severe cholestasis. Defining the spectrum of lesions of elapid snake envenomation improves understanding of the pathogenesis, which may lead to improved patient outcomes and post-mortem diagnosis.